Invasive hemodynamics are equivocal for functional outcomes after MitraClip. Issue 1 (12th January 2022) - Power, Juliette E.; Reiff, Chris; Tsangaris, Adamantios; Hall, Alexandra; Raveendran, Ganesh; Yannopoulos, Demetris; Gurevich, Sergey
Abstract: Objectives: To evaluate invasive hemodynamics in assessing MC therapy success as well as evaluate its effectiveness as a predictor of functional outcomes. Background: Mitral regurgitation grade is a poor predictor of functional outcomes after a MitraClip. There is a paucity of data on invasive hemodynamics as a predictor of outcomes. Methods: Sixty‐nine patients underwent MC between 2015 and 2018 at the University of Minnesota Medical Center and were retrospectively analyzed. Invasive hemodynamics were performed before and after device deployment with transesophageal echocardiographic guidance. Statistical analysis was performed using STATA version 16. Student's t test was used for continuous variables and Pearson's chi‐squared test for categorical variables. Mann‐Whitney test was performed for continuous variables where data were not normally distributed. Logistic and linear regression were used to investigate relationships between variables and outcomes. Results: A total of 69 patients were included in the study. The mean age was 83 (75‐87) years and 38 (55%) were male. Eighty‐one percentage had >/= NYHA III symptoms. Eighty‐seven percentage had severe MR. Pulmonary capillary wedge pressure was 20 (15‐24). Overall, there was significant improvement in left atrial pressure including mean left atrial pressure index, MR, and NYHA class after MC (<.001). There was no significant association between invasive hemodynamics (including left atrial mean pressure index or its reduction rate) and functional outcomes (p = NS). MR grade was also not predictive of functional outcomes. Conclusion: Left atrial pressure may not be a significant predictor of functional outcomes, and, in isolation, may not be an improvement over MR grade.